2021
DOI: 10.1093/brain/awab268
|View full text |Cite
|
Sign up to set email alerts
|

The role of mTORC1 activation in seizure-induced exacerbation of Alzheimer's disease

Abstract: Seizure risk is 10-fold higher in Alzheimer’s disease patients than the general population, yet the mechanisms underlying this susceptibility and the effects of seizures on Alzheimer’s disease are poorly understood. To elucidate our proposed bidirectional relationship between Alzheimer’s disease and seizures, we studied Alzheimer’s disease human brain samples (n = 34) and found that patients with a history of seizures (n = 14) had increased β-amyloid and tau pathology, and upregulation of the mechanistic targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 101 publications
11
49
0
Order By: Relevance
“…However, the connection between mTOR overactivity and AMPA receptor potentiation [ 13 ] allows us to consider the perspective of toning down the deleterious activity of AMPA receptors within the piriform cortex by suppressing mTOR. This is in line with data showing that seizures may be considered “mTORpathies,” and mTOR overexpression may foster the onset of SE [ 14 - 16 ]. The protein complex mTOR was previously defined as the “mammalian target of rapamycin,” and it is now defined as a “mechanistic target of rapamycin.” This occurs in two structurally and functionally distinct complexes, mTORC1 and mTORC2.…”
Section: Introductionsupporting
confidence: 89%
“…However, the connection between mTOR overactivity and AMPA receptor potentiation [ 13 ] allows us to consider the perspective of toning down the deleterious activity of AMPA receptors within the piriform cortex by suppressing mTOR. This is in line with data showing that seizures may be considered “mTORpathies,” and mTOR overexpression may foster the onset of SE [ 14 - 16 ]. The protein complex mTOR was previously defined as the “mammalian target of rapamycin,” and it is now defined as a “mechanistic target of rapamycin.” This occurs in two structurally and functionally distinct complexes, mTORC1 and mTORC2.…”
Section: Introductionsupporting
confidence: 89%
“…We and others have demonstrated bidirectional interactions with AD and epilepsy sharing similar pathology and convergence upon common underlying cellular mechanisms. Human temporal lobe epilepsy brain tissue shows increased Aβ plaques and increased hyperphosphorylated tau (pTau) (Gourmaud et al 2020; Thom et al 2011; Tai et al 2016) and the accumulation of these neuropathological proteins in AD animal models are associated with elevated neuronal hyperexcitability and seizure susceptibility (Palop and Mucke 2009; Westmark et al 2008; DeVos et al 2013; Johnson, Ho, et al 2020; Chang et al 2021; Gourmaud et al 2022). Indeed, development of late-onset epilepsy substantially increases dementia risk and accelerates the rate of cognitive decline (Johnson, Krauss, Kucharska-Newton, et al 2020; Johnson, Krauss, Walker, et al 2020; Kawakami et al 2018; Keret et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Considering these data and that rapamycin and other rapalogs are approved by the United States Food and Drug Administration for other indications, mTORC1 is a promising target for therapeutic intervention for patients with AD and co-morbid epilepsy. In a recent study, we found that AD patients with a history of seizure display elevated tau and Aβ pathology, associated with increased mTORC1 activity (Gourmaud et al 2022). In addition, we observed that the induction of seizures in the five times familial AD (5XFAD) mice exacerbates Aβ pathology and cognitive deficits, and that these changes are reversible with chronic low-dose rapamycin treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations